Penerapan Internet of Thinks (IoT) Pada Alat Monitoring Energi Listrik - Tanto; Darmuji (LPPM Politeknik Jambi, 2019)
The purpose of this study is to monitor household electricity consumption based on Arduino, Esp and Android, which can be monitored through smartphones so that there is no soaring costs when paying electricity every month. The test sample is the use of 5 watts of light and solder simultaneously, to see the number of watts used and expenditure at the time of use with a monitoring system on smartphones which is equipped with applications connected via the Arduino system using the ESP8266 module as data sender so that we can monitor via a smartphone and this tool is equipped with an LCD on the display so that we can monitor in two views.